Simultaneous treatment of fruit juice industry wastewater and single-cell protein synthesis using purple non-sulfur bacteria - Naim Rashid (15044240) (2022)
Fruit juice industry wastewater is characterized by high chemical oxygen demand (COD) and low pH, which requires extensive energy if treated aerobically and can adversely affect aquatic organisms if discharged into water bodies without proper treatment. In this study, purple non-sulfur bacteria (PNSB) were employed to recover carbon through photoanaerobic treatment in the form of single-cell protein (SCP) suitable for aquaculture and rich in carotenoid and bacteriochlorophyll photopigments. The efficacy of PNSB was investigated using two types of wastewaters, citrus juice wastewater (CJW), and mixed juice wastewater (MJW) as substrates at different pH conditions (5.0–8.0). pH 8.0 showed the highest COD removal in CJW (89 ± 0.1%) and pH 7.0 in MJW (94 ± 1%), respectively. The biomass yields were 0.493 g-VSS·g-COD−1 and 0.397 g-VSS·g-COD−1 for CJW and MJW. SCP contents in CJW and MJW were 48 ± 1% and 40 ± 3%, respectively. Pigment analysis revealed that PNSB biomass contained carotenoids and bacteriochlorophyll. Carotenoids in CJW and MJW were 1354 ± 64 µg·g−1 and 1558 ± 218 µg·g−1 of biomass; bacteriochlorophyll contents were 2097 ± 110 µg·g−1 and 3100 ± 614 µg·g−1 of biomass, respectively. The microbial population showed diversity among the two substrates and pH conditions, with PNSB comprising potentially up to 51% of microbes in the culture. The results demonstrate that PNSB could be used as potential mediators to treat fruit juice wastewater, and produce SCP, and photopigments simultaneously. Other Information Published in: Biomass Conversion and Biorefinery License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s13399-022-03669-6